Genome-wide analysis of the hard clam mitogen-activated protein kinase kinase gene family and their transcriptional profiles under abiotic stress. (April 2022) - Hu, Zhi; Song, Hao; Feng, Jie; Zhou, Cong; Yang, Mei-Jie; Shi, Pu; Yu, Zheng-Lin; Li, Yong-Ren; Guo, Yong-Jun; Li, Hai-Zhou; Wang, Su-Yao; Xue, Jiang-Han; et al.
Abstract: Mitogen-activated protein kinase kinase (MAPKK) was the hub component of the Mitogen-activated protein kinase (MAPK) signaling pathway and played an important role in the cellular response to environmental stress. In this study, we identified five MmMAPKK genes in hard clam Mercenaria mercenaria and found that all MmMAPKK genes contain a conserved protein kinase domain. The MmMAPKK genes derived from dispersed duplication were unevenly distributed in three chromosomes. Although the genome size was highly variable among different bivalve mollusks, the number of MAPKK genes was relatively stable. Phylogenetic analysis showed that bivalve MAPKK was divided into five clades, and amino acid sequences of MAPKK from the same clade consisted of similar conserved motifs. The syntenic analysis demonstrated that MmMAPKKs had the highest number of homologous gene pairs with Cyclina sinensis . MmMAPKKs were ubiquitously expressed in all examined tissues, and all MmMAPKK genes were highly expressed in the ovary. MmMAPKK genes showed stress-specific expression under envirionmental stress. MmMAPKK7 showed an upregulated in heat and heat plus hypoxia stress while MmMAPKK1 showed an upregulated in hypoxic stress groups. Dynamic changes of MmMAPKK7, MmMAPKK6 and MmMAPKK1 in hemocytes were observed in response to air exposure. MmMAPKK4 significantly downregulated after air exposure for five days. MmMAPKK7 and MmMAPKK6 might participate in adaptation to low salinity stress. Our results provided useful information about MAPKK and laid a foundation for further studies on MAPKK evolution in the bivalve. Highlights: Five MmMAPKK genes were identified in hard clam. MAPKK from the same clade consisted of similar conserved motifs. The expression of MmMAPKK genes under environmental stress was explored.